Struktur, Kategori, dan Fungsi Pertanyaan Tradisional di Nagari Tandikat Kabupaten Padang Pariaman - Irfan Hasyim; Muhammad Adek (Persona: Kajian Bahasa dan Sastra, 2022)
The purupose of this research is to describe the structure categories and function of traditional questions in Nagari Tandikat Kabupaten Padang Pariaman as well as an effort to documentation traditional questions so they are forgotten. The technique used for data collection is divided into three, namely: (1) develop interview guidelines for informants, (2) conducting direct interviews with informants using realme c15 cellphones in the form of voice recordings, used to obtain data on traditional questions, (3) library studies, are used to obtain references that can support research. This research method uses the descriptive method. While the data analysis method uses descriptive analysis method. This research yielded several findings, namely traditional questions have two structures: questions and answers, based on the 11 categories traditional questions five categories of traditional questions were found, in addition traditional questions serve to test one’s intelligence and as entertainment.